THE DEVELOPMENT AND VALIDITY OF MINDFULNESS DHIKR BREATHING THERAPY FOR INSOMNIA - Setiyo Purwanto; Mahadir Ahmad; Zaini Said; Nisa Rachmah Nur Anganthi; Mutalazimah; Siti Zulaekah (The Indonesian Journal of Public Health, 2023)
Introduction: The prevalence of insomnia in Indonesia is still quite high around 10% to 38.5%. Mindfulness is one of the therapeutic models that can overcome the weaknesses of previous therapeutic for insomnia. Muslims need therapy that uses elements of Islam to feel the benefits. Aim: to develop mindfulness dhikr breathing therapy for insomnia. In this study, we assess the face validity, content validity, and acceptability of the module and audio recording of the mindfulness dhikr breathing therapy. Methods: This research is part of a research and development model of mindfulness dhikr breathing therapy for insomniacs. Participant for the validity test was five experts in psychology. Participants for the acceptability test were 13 adults who suffered from insomnia. The object assessed was the module and audio recording of the therapeutical model. Analysis of face validity was using the subjective valuation by the rater. Analysis of content validity used Aiken's V coefficient. Result: From the rater's subjective assessment of the therapy module and audio recording of the therapy several suggestions were obtained. The content validity based on the average Aiken V coefficient was 0.99 (>0.84, p=0.021). The acceptability obtained average rating for all aspects of the acceptance assessment was 4,30 (>3). Conclusion: The mindfulness dhikr breathing therapy is worthy of use and acceptable as a therapeutic for insomnia. Researchers hope that the development of the module and audio recording of mindfulness dhikr breathing therapy can help the implementation of therapy so that it can be more optimal in overcoming insomnia.